Heat-proof and heat-insulation paint, coating and preparation method thereof

By using homemade "Paracum" functionally modified lightweight thermal insulation filler, the problems of large thickness and poor molding uniformity of ablation and heat-proof coating are solved, and the preparation of large-size ultra-thin coatings is realized, with the characteristics of low thermal conductivity, high pulling strength and high temperature resistance.

CN119505698AActive Publication Date: 2025-02-25AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH

Patent Information

Application Number
CN202411829893.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-25
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing ablation and heat insulation coating has a large thickness, making it difficult to achieve uniformity of large-size coating molding and control of primary molding accuracy.

Method used

The homemade "Paracum" type functionally modified lightweight heat-insulating filler is used to replace traditional hollow microspheres, high emissivity powders, etc., and by reducing the thermal conductivity of the coating and improving the compatibility between the base glue and the filler, the coating composition is simplified and the forming of the ultra-thin coating is achieved.

Benefits of technology

The preparation of large-size ultra-thin anti-heat insulation coating is achieved, with low coating density, reduced thermal conductivity, and improved pulling strength, which can withstand high temperatures and maintain good thermal insulation performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a heat-proof and heat-insulating coating, a coating and a preparation method thereof, and relates to the field of heat-proof and heat-insulating coatings. The self-made functional modified light heat-insulating filler, the ceramic forming filler and the photosensitive modified matrix film forming matter are mixed and cured to obtain the heat-proof and heat-insulating coating. A coating layer obtained from the prepared coating is based on the functional modified light heat insulation filler, large-size coating forming and uniform forming can be achieved on the basis that the excellent three-dimensional structure and performance are kept, high-strength combination with a base material is achieved, and the temperature resistance and heat insulation performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heat-insulating coatings, and in particular to a heat-insulating coating, a coating and a preparation method thereof. Background Art

[0002] Thermal insulation coatings have important applications in the field of high-temperature thermal insulation and can provide thermal protection for the outer surface of materials. As a special type of thermal insulation coating, ablative thermal insulation coatings can dissipate heat through thermal degradation or ablation of the coating itself or the coating formed by coating, thereby achieving thermal protection of the material. Generally speaking, in order for ablative thermal insulation materials to achieve better heat protection and thermal insulation properties, it is necessary to ensure that they have sufficient ablative components to achieve heat dissipation through mass induced emission, as well as sufficient thickness to achieve thermal insulation protection for the substrate.

[0003] Different from general paint films and other functional coatings, in order to achieve thermal protection in a long-term aerobic environment, ablative coating materials usually have a high thermal conductivity (~0.15W / (m·K)), and require a certain thickness (generally 3-5mm) to achieve a good protective effect, which reduces the efficiency of coating formation; at the same time, in order to achieve effective heat dissipation, its composition is usually more complex, generally including organic ablative components, carbon-forming components, inorganic components, functional components, etc. These components have large differences in properties and poor compatibility. In the actual coating and forming process, it is very easy to cause defects such as orange peel and holes due to local uneven agglomeration, which is not conducive to rapid large-area coating and application. In addition, due to the properties of the coating matrix, the bonding force between it and the base material is generally low, and it is not resistant to airflow erosion. In actual application, it is often enhanced by adding an additional primer to increase the coating construction process. Therefore, in order to address the current problems of large thickness of ablation anti-thermal insulation coatings, uniformity of large-size coating molding, and high precision control of one-time molding, the coating formula is optimized and combined with a certain coating process to achieve large-size uniform ultra-thin anti-thermal insulation coating molding, and prepare large-size ultra-thin anti-thermal insulation coating materials, which is of great significance for the research and development of high-temperature thermal protection materials. Summary of the invention

[0004] The purpose of the present invention is to provide a heat-insulating coating, a coating and a preparation method thereof, so as to solve the problems of the current ablative heat-insulating coating having a large thickness (generally > 1 mm), the difficulty in uniformity of large-size coating molding and the difficulty in controlling the precision of one-time molding. The heat-insulating coating replaces the traditional hollow microspheres, high-emissivity powders, carbon-forming components, fibers and whisker-reinforced fillers with homemade "paramecium" type functionally modified lightweight heat-insulating fillers, integrates heat-insulating, light-weight, reinforced, high-emissivity and carbon-forming ablative components, reduces the coating thermal conductivity, reduces the coating thickness (~1 mm), improves the overall compatibility of the coating base glue and the filler, has a simple coating method, and has high one-time molding quality, and has important application prospects in the field of heat-insulating coatings.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a heat-insulating coating, the method comprising the following steps:

[0007] (1) First, short rod-shaped quartz hollow microspheres are prepared; then a layer of infrared high emissivity material is coated on the surface of the microspheres, and after drying, the microspheres are shaken and dispersed to obtain a base material; catalyst particles are loaded on the base material, and then nano-carbon materials are grown, and after drying, the microspheres are shaken and dispersed to obtain a base material; then, a photosensitizer is loaded on the surface of the base material to obtain a functionally modified lightweight thermal insulation filler;

[0008] (2) According to the weight ratio, 10 to 80 parts of functional modified lightweight thermal insulation filler, 15 to 50 parts of ceramic filler and 60 to 120 parts of base film-forming material are mixed evenly to prepare a thermal insulation coating base material;

[0009] (3) Add a curing agent, a photoinitiator and a diluent to the heat-insulating coating base material, stir and mix them evenly to obtain the heat-insulating coating.

[0010] Preferably, the short rod-shaped hollow quartz microspheres in step (1) have a diameter of 50 to 100 μm, a length of 100 to 200 μm, and a density of 0.03 to 0.08 g / cm 3 .

[0011] Preferably, in step (1), the infrared high emissivity material is one or more of silicon carbide, spinel ferrite, cerium oxide, and yttrium oxide, and the coating thickness is 1 to 10 μm.

[0012] Preferably, the catalyst in step (1) is one or more of salts and metal clusters, and the salts and metal clusters contain at least one element of iron, cobalt and nickel, and the catalyst loading is 0.05% to 2% of the mass of the substrate material.

[0013] Preferably, the size of the nano-carbon material grown in step (1) is 10 to 50 μm.

[0014] Preferably, in step (1), the photosensitizer is one of benzophenone, benzyl and Michler's ketone, and the loading amount is 5-10% of the mass of the substrate material.

[0015] Preferably, in step (1), the powder is dispersed by oscillation through ball milling.

[0016] Preferably, the ceramic filler in step (2) is a compound of one or more of nano-silicon dioxide aerogel, nano-alumina, mica powder, talc powder and one or more of sodium oxide powder, potassium oxide powder, boron oxide powder, iron oxide powder, phosphorus oxide powder, zinc oxide powder, manganese oxide powder and zirconium oxide powder.

[0017] Preferably, the particle size of the ceramic filler in step (2) is ≥100 mesh.

[0018] Preferably, the matrix film-forming material in step (2) is one or more of modified silicone rubber containing photosensitive prepolymer, silicone resin containing photosensitive prepolymer, epoxy resin containing photosensitive prepolymer, and phenolic resin containing photosensitive prepolymer, and the photosensitive prepolymer is one or more of polyurethane, unsaturated polyester, and acrylic resin.

[0019] Preferably, in step (2), when mixing, the viscosity is adjusted by adding 10% to 30% by weight of a solvent, and the solvent is one or more of cyclohexane, ethyl acetate, butyl acetate, petroleum ether, No. 60 solvent oil, and No. 120 solvent oil.

[0020] Preferably, in step (2), the functional modified lightweight thermal insulation filler is 15 to 65 parts, the ceramic filler is 25 to 35 parts, and the matrix film-forming material is 70 to 110 parts.

[0021] Preferably, the curing agent in step (3) is one of organic tin, amines, and organic bases. The corresponding curing agent is selected according to the substrate film-forming material used, and the added amount of the curing agent is calculated as 1%-10% of the added mass of the substrate film-forming material.

[0022] Preferably, the photoinitiator in step (3) is one of benzophenone, acetophenone, benzoin, and benzoin derivatives, and the added amount is calculated based on 2% to 5% of the substrate film-forming material.

[0023] Preferably, after the curing agent is added and mixed evenly in step (3), the coating needs to be used within 2 to 5 hours depending on the curing system.

[0024] Preferably, the diluent in step (3) is a small amount of one or more of ethanol, methanol, and n-pentanol, mixed with one or more of acetone, cyclohexane, ethyl acetate, butyl acetate, toluene, xylene, petroleum ether, No. 60 solvent oil, and No. 120 solvent oil.

[0025] In a second aspect, the present invention provides an anti-heat-insulating coating, which is prepared by the method described in the first aspect of the present invention.

[0026] The present invention provides a heat-insulating coating in a third aspect, which is a coating formed by the heat-insulating coating prepared by the method described in the first aspect of the present invention. The preparation steps of the coating include: diluting the prepared coating with a diluent to a suitable viscosity, using a suitable brushing method, completing the entire brushing process on the base material, and obtaining a large-sized ultra-thin heat-insulating coating after drying.

[0027] Preferably, the coating method is scraping or spraying.

[0028] Preferably, the drying method is air-drying at room temperature and pressure combined with ultraviolet irradiation for 2-4 days.

[0029] Compared with the prior art, the method of the present invention has the following beneficial effects:

[0030] (1) The large-sized ultra-thin heat-insulating coating prepared by the present invention adopts a self-made "Paramecium" type functional modified lightweight heat-insulating filler to replace the traditional hollow microspheres, high-emissivity powders, carbon-forming components, fibers and whisker reinforced fillers, and integrates heat-insulating, lightweight, reinforced, high-emissivity and carbon-forming ablation components to achieve functional integration and greatly simplify the coating composition; at the same time, the functional integrated filler can significantly reduce the thermal conductivity of the coating through ablation heat absorption, melting heat absorption, infrared emission heat dissipation and hollow insulation, and thus reduce the thickness of the ablation coating. The thickness of the traditional coating can be reduced by more than 50%, and the preparation of large-sized coatings with a thickness of less than 1 mm can be achieved.

[0031] (2) The large-sized ultra-thin heat-insulating coating prepared by the present invention adopts a self-made matrix film-forming material containing a photosensitive prepolymer. In addition to normal curing and cross-linking, the coating is further cross-linked inside by means of a photocuring method to improve the strength and shape-maintaining ability of the coating, thereby ensuring that the coating still has good heat-insulating performance under relatively thin conditions.

[0032] (3) The large-size ultra-thin heat-insulating coating prepared by the present invention has a simple mixing method, and the finished product is uniform and stable. The prepared heat-insulating layer has good overall uniformity and flatness, and has a low density (less than 0.5 g / cm 3 ), room temperature thermal conductivity is 0.04-0.08W / (m·K), room temperature tensile strength is ≥1MPa, temperature resistance is ≥1000℃, service time is ≥60s, it can maintain a low mass loss rate during service, can effectively reduce the coating surface density, meet the lightweight requirements of thermal insulation materials, and the coating process is simple, which is of great significance for the research and development of high-temperature thermal protection materials. DETAILED DESCRIPTION

[0033] In order to make the various technical features and advantages or technical effects in the above technical solutions of the present invention more obvious and easy to understand, they are described in detail below in conjunction with embodiments.

[0034] Embodiment 1:

[0035] (1) First, short rod-shaped quartz hollow microspheres with a diameter of 50 μm and a length of 100 μm are prepared, a layer of 5 μm silicon carbide material is deposited on the outer surface of the microspheres, and after drying into blocks, a layer of ferric chloride salt with a mass fraction of 1% of the above material is shaken and dispersed into a monodisperse state; then, a layer of nanocarbon material is grown by chemical vapor deposition, and the size of the grown nanocarbon material is 20 to 30 μm by controlling the reaction conditions, and then the material is shaken and dispersed to obtain a base material; finally, 5% of benzophenone is loaded on the surface of the above base material to obtain a functionally modified lightweight thermal insulation filler;

[0036] (2) 80 g of functional modified lightweight thermal insulation filler, 50 g of porcelain filler (10 g of nano-alumina, 10 g of mica powder, 10 g of boron oxide, 10 g of potassium oxide and 10 g of zirconium oxide) and 120 g of modified room temperature vulcanized silicone rubber (containing 20% ​​by mass of polyurethane) were mixed evenly, and 50 g of cyclohexane was added during the mixing to adjust the viscosity, thereby preparing a thermal insulation coating base material;

[0037] (3) Add 6 g of dibutyltin dilaurate and 2.4 g of benzophenone to the above-mentioned heat-insulating coating base material, stir and mix evenly to obtain the heat-insulating coating.

[0038] The above coating was diluted with cyclohexane and then applied to a 5mm thick coating component, dried at room temperature and irradiated with ultraviolet light for 3 days before conducting relevant assessments.

[0039] Product performance test: The density of the prepared coating is 0.45g / cm 3 The room temperature thermal conductivity is 0.053W / (m·K), the greenhouse tensile strength is 2.5MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 3.5×10 -4 g / s, and the outer surface of the coating remains intact after the test.

[0040] Embodiment 2:

[0041] (1) First, short rod-shaped quartz hollow microspheres with a diameter of 100 μm and a length of 200 μm are prepared, and a layer of yttrium oxide material with a thickness of 10 μm is deposited on the outer surface of the microspheres. After drying into blocks, the materials are shaken and dispersed into a monodisperse state; then, 2% nickel nitrate by mass fraction of the materials is loaded on the surface of the materials, and then a layer of nanocarbon material is grown by chemical vapor deposition. By controlling the reaction conditions, the size of the grown nanocarbon material is 40 to 50 μm, and then the materials are shaken and dispersed to obtain a base material; finally, 10% benzyl by mass fraction is loaded on the surface of the base material to obtain a functionally modified lightweight thermal insulation filler;

[0042] (2) 80 g of functional modified lightweight thermal insulation filler, 40 g of porcelain filler (20 g of nano-alumina, 5 g of mica powder, 5 g of boron oxide, 5 g of potassium oxide and 5 g of zirconium oxide) and 100 g of modified silicone resin (containing 30% by mass of polyacrylic acid resin) were mixed evenly, and 60 g of ethyl acetate was added during mixing to adjust the viscosity to prepare a thermal insulation coating base material;

[0043] (3) Add 5 g of tetramethylammonium hydroxide and 2.4 g of benzophenone to the above-mentioned thermal insulation coating base material, stir and mix evenly to obtain the thermal insulation coating.

[0044] The above-mentioned coating was diluted with No. 120 solvent oil, and then applied to a 5mm thick coating component, dried at room temperature, and irradiated with ultraviolet light for 3 days before conducting relevant assessments.

[0045] Product performance test: The density of the prepared coating is 0.43g / cm 3 The room temperature thermal conductivity is 0.063W / (m·K), the greenhouse tensile strength is 2.7MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 4.2×10 -4 g / s, and the outer surface of the coating remains intact after the test.

[0046] Embodiment 3:

[0047] (1) First, short rod-shaped hollow quartz microspheres with a diameter of 50 μm and a length of 100 μm are prepared, and a layer of 1 μm cerium oxide material is deposited on the outer surface of the microspheres. After drying into blocks, the materials are shaken and dispersed into a monodisperse state; then, 0.05% cobalt tungstate by mass fraction of the materials is loaded on the surface of the materials, and then a layer of nanocarbon material is grown by chemical vapor deposition. By controlling the reaction conditions, the size of the grown nanocarbon material is 10 μm, and then the materials are shaken and dispersed to obtain a base material; finally, 5% Michler's ketone by mass fraction is loaded on the surface of the base material to obtain a functionally modified lightweight thermal insulation filler;

[0048] (2) 10 g of functional modified lightweight thermal insulation filler, 15 g of porcelain filler (5 g of nano-alumina, 3 g of mica powder, 2 boron oxide, 2 g of potassium oxide, 2 g of zirconium oxide and 1 g of phosphorus oxide) and 60 g of phenolic resin (containing 30% by mass of polyacrylic acid resin) were mixed evenly, and 8.5 g of petroleum ether was added during the mixing to adjust the viscosity, thereby preparing a thermal insulation coating base material;

[0049] (3) Add 7.2 g of hexamethylenetetramine and 1.2 g of acetophenone to the above-mentioned thermal insulation coating base material, stir and mix evenly to obtain the thermal insulation coating.

[0050] The above-mentioned coating was diluted with No. 120 solvent oil, and then applied to a 5mm thick coating component, dried at room temperature, and irradiated with ultraviolet light for 3 days before conducting relevant assessments.

[0051] Product performance test: The density of the prepared coating is 0.35g / cm 3 The room temperature thermal conductivity is 0.045W / (m·K), the greenhouse tensile strength is 1.7MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 2.1×10 -4 g / s, and the outer surface of the coating remains intact after the test.

[0052] Embodiment 4:

[0053] (1) First, short rod-shaped quartz hollow microspheres with a diameter of 50 μm and a length of 100 μm are prepared, a layer of 5 μm cerium oxide material is deposited on the outer surface of the microspheres, and after drying into blocks, it is shaken and dispersed into a monodisperse state; then, 0.1% of ferrous oxide and 0.1% of cobalt oxide are loaded on the surface of the above material by mass fraction, and then a layer of nanocarbon material is grown by chemical vapor deposition. By controlling the reaction conditions, the size of the grown nanocarbon material is 10 μm, and then the material is shaken and dispersed to obtain a base material; finally, 10% of Michler's ketone is loaded on the surface of the above base material by mass fraction to obtain a functionally modified lightweight thermal insulation filler;

[0054] (2) 15 g of functional modified lightweight thermal insulation filler, 25 g of porcelain filler (5 g of nano-alumina, 5 g of mica powder, 5 g of boron oxide, 5 g of potassium oxide, 3 g of zirconium oxide and 2 g of phosphorus oxide) and 70 g of modified silicone resin (containing 30% by mass of polyacrylic acid resin) were mixed evenly, and 11 g of petroleum ether was added during the mixing to adjust the viscosity to prepare a thermal insulation coating base material;

[0055] (3) Add 7 g of tetrabutyl titanate and 3 g of benzoin to the above-mentioned heat-insulating coating base material, stir and mix evenly to obtain the heat-insulating coating.

[0056] The above coating was diluted with butyl acetate and then applied to a 5mm thick coating component, dried at room temperature and irradiated with ultraviolet light for 2 days before conducting relevant assessments.

[0057] Product performance test: The density of the prepared coating is 0.30g / cm 3 The room temperature thermal conductivity is 0.040W / (m·K), the greenhouse tensile strength is 1.5MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 1.1×10 -4 g / s, and the outer surface of the coating remains intact after the test.

[0058] Embodiment 5:

[0059] (1) First, short rod-shaped quartz hollow microspheres with a diameter of 50 μm and a length of 100 μm are prepared, a layer of 5 μm spinel ferrite is deposited on the outer surface of the microspheres, and after drying into blocks, a layer of ferrous oxide and cobalt oxide with a mass fraction of 1% are loaded on the surface of the above material, and then a layer of nanocarbon material is grown by chemical vapor deposition, and the size of the grown nanocarbon material is 50 μm by controlling the reaction conditions, and then the material is shaken and broken up to obtain a base material; finally, a layer of Michler's ketone with a mass fraction of 10% is loaded on the surface of the above base material to obtain a functionally modified lightweight thermal insulation filler;

[0060] (2) 65 g of functional modified lightweight thermal insulation filler, 35 g of porcelain filler (5 g of nano-alumina, 5 g of mica powder, 5 g of talc, 5 g of boron oxide, 5 g of potassium oxide, 5 g of zirconium oxide and 5 g of phosphorus oxide) and 110 g of modified silicone resin (containing 20% ​​by mass of unsaturated polyester) were mixed evenly, and 60 g of No. 120 solvent oil was added during the mixing to adjust the viscosity to prepare a thermal insulation coating base material;

[0061] (3) Add 10 g of tetrabutyl titanate and 6 g of benzoin to the above-mentioned heat-insulating coating base material, stir and mix evenly to obtain the heat-insulating coating.

[0062] The above-mentioned coating was diluted with No. 120 solvent oil, and then applied to a 5mm thick coating component, dried at room temperature, and irradiated with ultraviolet light for 2 days before conducting relevant assessments.

[0063] Product performance test: The density of the prepared coating is 0.50g / cm 3 The room temperature thermal conductivity is 0.078W / (m·K), the greenhouse tensile strength is 3.5MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 5.1×10 -4 g / s, and the outer surface of the coating remains intact after the test.

[0064] Comparative Example 1:

[0065] (1) 40 g of hollow glass microspheres, 20 g of chopped quartz fibers, 20 g of chopped high-silica fibers, 50 g of ceramic filler (10 g of nano-alumina, 10 g of mica powder, 10 g of boron oxide, 10 g of potassium oxide and 10 g of zirconium oxide) and 120 g of room temperature vulcanized silicone rubber were mixed evenly, and 50 g of cyclohexane was added during the mixing to adjust the viscosity to prepare a heat-insulating coating base material;

[0066] (2) Add 6 g of dibutyltin dilaurate to the above-mentioned heat-insulating coating base material, stir and mix evenly to obtain the heat-insulating coating.

[0067] The above coating was diluted with cyclohexane and then applied to a 5mm thick coating component. It was dried at room temperature and relevant assessments were conducted after 3 days.

[0068] Product performance test: The density of the prepared coating is 0.30g / cm 3 The room temperature thermal conductivity is 0.033W / (m·K), the greenhouse tensile strength is 0.5MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 12×10 -4 g / s, after the test, the coating surface cracked and fell off.

[0069] Comparative Example 2:

[0070] (1) 30 g of hollow glass microspheres, 15 g of chopped quartz fibers, 20 g of chopped high-silica fibers, 35 g of porcelain fillers (5 g of nano-alumina, 5 g of mica powder, 5 g of talc, 5 g of boron oxide, 5 g of potassium oxide, 5 g of zirconium oxide, and 5 g of phosphorus oxide) and 110 g of silicone resin were mixed evenly, and 60 g of No. 120 solvent oil was added during the mixing to adjust the viscosity to prepare a heat-insulating coating base material;

[0071] (2) Add 10 g of tetrabutyl titanate to the above-mentioned thermal insulation coating base material, stir and mix evenly to obtain the thermal insulation coating.

[0072] The above paint was diluted with No. 120 solvent oil, then applied to 5mm thick coating components, dried at room temperature, and relevant assessments were conducted after 2 days.

[0073] Product performance test: The density of the prepared coating is 0.32g / cm 3 The room temperature thermal conductivity is 0.035W / (m·K), the greenhouse tensile strength is 0.4MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 14×10 -4 g / s, after the test, the coating surface cracked and fell off.

[0074] Comparative Example 3:

[0075] (1) 10 g of hollow glass microspheres, 5 g of chopped quartz fibers, 25 g of ceramic filler (5 g of nano-alumina, 5 g of mica powder, 5 g of boron oxide, 5 g of potassium oxide, 3 g of zirconium oxide and 2 g of phosphorus oxide) and 70 g of silicone resin were mixed evenly, and 11 g of petroleum ether was added during the mixing to adjust the viscosity to prepare a heat-insulating coating base material;

[0076] (3) Add 7 g of tetrabutyl titanate to the above-mentioned thermal insulation coating base material, stir and mix evenly to obtain the thermal insulation coating.

[0077] The above coating was diluted with butyl acetate and then applied to a 5mm thick coating component. It was dried at room temperature and relevant assessments were conducted after 2 days.

[0078] Product performance test: The density of the prepared coating is 0.25g / cm 3 The room temperature thermal conductivity is 0.031W / (m·K), the greenhouse tensile strength is 0.4MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 13×10 -4 g / s, after the test, the coating surface cracked and fell off.

[0079] Comparative Example 4:

[0080] (1) 8 g of hollow glass microspheres, 2 g of chopped quartz fibers, 15 g of ceramic filler (5 g of nano-alumina, 3 g of mica powder, 2 boron oxide, 2 g of potassium oxide, 2 g of zirconium oxide, and 1 g of phosphorus oxide) and 60 g of phenolic resin were uniformly mixed, and 8.5 g of petroleum ether was added during the mixing to adjust the viscosity to prepare a heat-insulating coating base material;

[0081] (3) Add 7.2 g of hexamethylenetetramine to the above-mentioned thermal insulation coating base material, stir and mix evenly to obtain the thermal insulation coating.

[0082] The above paint was diluted with No. 120 solvent oil, then applied to 5mm thick coating components, dried at room temperature, and relevant assessments were conducted after 3 days.

[0083] Product performance test: the density of the prepared coating is 0.33g / cm 3 The room temperature thermal conductivity is 0.042W / (m·K), the greenhouse tensile strength is 0.6MPa, it can withstand 1000℃ oxyacetylene test for 100s, and the mass ablation rate is 14×10 -4 g / s, after the test, the coating surface cracked and fell off.

[0084] It can be seen from the above-mentioned Examples 1-5 and Comparative Examples 1-4 that, compared with the comparative examples, the embodiments are in a state that, since the functionally modified lightweight thermal insulating filler is prepared through the first step and the filler is mixed with the coating base material, the coating finally prepared, after being made into a coating product, integrates the filler function while reducing the thermal conductivity of the coating, reducing the coating thickness, and improving the overall compatibility between the coating base glue and the filler. The coating method is simple and the one-time molding quality is high.

[0085] Although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions of the technical solutions of the present invention made by ordinary technicians in the field should all be included in the protection scope of the present invention. The protection scope of the present invention shall be based on what is defined in the claims.

Claims

1. A method for preparing a heat-insulating coating, characterized in that: The following steps are involved: (1) First, short rod-shaped quartz hollow microspheres are prepared; then a layer of infrared high emissivity material is coated on the surface of the microspheres, and after drying, the microspheres are shaken and dispersed to obtain a base material; catalyst particles are loaded on the base material, and then nano-carbon materials are grown, and after drying, the microspheres are shaken and dispersed to obtain a base material; then, a photosensitizer is loaded on the surface of the base material to obtain a functionally modified lightweight thermal insulation filler; (2) According to the weight ratio, 10 to 80 parts of functional modified lightweight thermal insulation filler, 15 to 50 parts of ceramic filler and 60 to 120 parts of base film-forming material are mixed evenly to prepare a thermal insulation coating base material; (3) Add a curing agent, a photoinitiator and a diluent to the heat-insulating coating base material, stir and mix them evenly to obtain the heat-insulating coating.

2. The method according to claim 1, characterized in that The short rod-shaped hollow quartz microspheres in step (1) have a diameter of 50 to 100 μm, a length of 100 to 200 μm, and a density of 0.03 to 0.08 g / cm 3 .

3. The method according to claim 1, characterized in that In step (1), the infrared high emissivity material is one or more of silicon carbide, spinel ferrite, cerium oxide, and yttrium oxide, and the coating thickness is 1 to 10 μm; The catalyst is one or more of salts and metal clusters, the salts and metal clusters both contain at least one element of iron, cobalt and nickel, and the catalyst loading is 0.05% to 2% of the mass of the substrate material; The size of the grown nanocarbon materials is 10 to 50 μm; The photosensitizer is one of benzophenone, benzyl and Michler's ketone, and the loading amount is 5-10% of the mass of the base material.

4. The method according to claim 1, characterized in that The ceramic filler in step (2) is a compound of one or more of nano-silicon dioxide aerogel, nano-alumina, mica powder, talc powder and one or more of sodium oxide powder, potassium oxide powder, boron oxide powder, iron oxide powder, phosphorus oxide powder, zinc oxide powder, manganese oxide powder and zirconium oxide powder; the particle size of the ceramic filler is ≥100 mesh.

5. The method according to claim 1, characterized in that In step (2), the base film-forming material is one or more of modified silicone rubber containing photosensitive prepolymer, silicone resin containing photosensitive prepolymer, epoxy resin containing photosensitive prepolymer, and phenolic resin containing photosensitive prepolymer, and the photosensitive prepolymer is one or more of polyurethane, unsaturated polyester, and acrylic resin.

6. The method according to claim 1, characterized in that In step (2), when mixing, the viscosity is adjusted by adding 10% to 30% by weight of a solvent, wherein the solvent is one or more of cyclohexane, ethyl acetate, butyl acetate, petroleum ether, No. 60 solvent oil, and No. 120 solvent oil.

7. The method according to claim 1, characterized in that In step (2), the functional modified lightweight heat-insulating filler is 15 to 65 parts, the ceramic filler is 25 to 35 parts, and the matrix film-forming material is 70 to 110 parts.

8. The method according to claim 1, characterized in that In step (3), the curing agent is one of organic tin, amines, and organic bases. The curing agent corresponding to the substrate film-forming material is selected according to the substrate film-forming material used. The amount of the curing agent added is calculated as 1%-10% of the mass of the added substrate film-forming material. The photoinitiator is one of benzophenone, acetophenone, benzoin, and benzoin derivatives, and the added amount is calculated based on 2% to 5% of the base film-forming material; The diluent is a mixture of a small amount of one or more of ethanol, methanol, and n-pentanol with one or more of acetone, cyclohexane, ethyl acetate, butyl acetate, toluene, xylene, petroleum ether, No. 60 solvent oil, and No. 120 solvent oil.

9. A heat-insulating coating, characterized in that: Prepared by the method according to any one of claims 1 to 8.

10. A heat-insulating coating, characterized in that: The anti-heat-insulating coating is prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Lightweight temperature-resistant heat-insulating camouflage paint, coating and preparation method thereof

    CN115627119A

  • Ablation-resistant thermal insulation paint, coating and preparation method thereof

    CN115820111A

  • Low-density high-toughness hard ablation heat-proof coating and preparation method thereof

    CN116875189A

  • Catalyst based on hollow silicon nanocapsule loading as well as preparation method and application thereof

    CN117643895A

  • Ultrathin solvent-free heat-insulating fireproof flame-retardant coating for aviation aluminum alloy device

    CN118109102A

Cited By

  • Application of alkenyl-terminated heptapolyphenyl POSS (Polyhedral Oligomeric Silsesquioxane) in preparation of ceramic organic silicon thermal insulation material

    CN116478409A

  • Application of Terminal Alkenyl Heptaphenyl POSS in the Preparation of Ceramed Organosilicon Thermal Insulation Materials

    CN116478409B